THE EFFECT OF DRINKING CATTLE FLOWER TEA ON WEIGHT REDUCTION AND CHOLESTEROL - Eddy Purnomo (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
Obesity and cholesterol are one of the problems that are very feared. People have tried various alternative treatments made from plant/herbal ingredients, one of which is butterfly pea flower tea (Clitoria ternatea). The aim of this study was to determine the effect of the frequency of drinking butterfly pea flower tea (Clitoria ternatea) on weight loss (BMI) and cholesterol. Experimental research design with pre and post-test design methods. Grouping groups using matching pairs. Data is collected by measuring height, weight (BMI), and blood tests in the form of cholesterol tests. The research population was all members of the Indonesian National Army, Military District Command of KODIM Yogyakarta City whose BMI was 25. The data analysis technique used the t test and multivariate test, with a significance level of 5%. The results of the analysis show that: 1) there is an influence of the frequency of drinking 2 times of butterfly pea flower tea on reducing Body Mass Index (BMI) with a p value 0.000 and, cholesterol with a p value 0.002, 2) There is an influence of the frequency of drinking 3 times of butterfly pea flower tea on reducing Body Mass Index (BMI) with a p value 0.000 and cholesterol with a p value 0.001, 3 ) There is an effect of the frequency of drinking 5 times of butterfly pea flower tea on reducing Body Mass Index (BMI) with a p-value 0.001 and cholesterol with a p value 0.000, 4) There is a difference in the effect of the frequency of drinking 2 times, 3 times and 5 times of butterfly pea flower tea on reducing Body Mass Index (BMI) with a p value 0.0004 and cholesterol with a p value 0.001.